PEMBERDAYAAN MASYARAKAT DENGAN KONSEP KAWASAN EKONOMI MASYARAKAT (KEM) PADA LAHAN GAMBUT DI KAMPUNG BANTALAN, KECAMATAN TEMBILAHAN, KABUPATEN INDRAGIRI HILIR, RIAU [COMMUNITY EMPOWERMENT WITH THE CONCEPT OF COMMUNITY ECONOMIC ZONE (KEM) ON THE PEATLAND IN KAMPUNG BANTALAN, TEMBILAHAN DISTRICT, INDRAGIRI REGENCY, RIAU] - Padil Padil; Yuslizar -; Rikawati -; Titi Antin (Jurnal Sinergitas PKM & CSR, 2018)
The era of globalization continues to press the poor with lower levels of economic life. Therefore, FLipMAS Batobo with FLipMAS Indonesia and CSR-SMEPP Pertamina (Persero) conduct an analysis approach, strategy that can be implemented to eliminate poverty. One of the strategies undertaken is the empowerment of society with the concept of Community Economic Area (KEM). After conducting survey and location analysis, Kampung Bantalan, Tembilahan Seberang Sub-district, Indragiri Hilir Regency became one of the locations of empowerment called KEM Pertamina Flip Bantalan. The empowerment activities began in December 2014 and the investment process was completed in June 2017 on a land area of ± 6 Ha which then expanded to ± 20 Ha. Programs implemented in KEM Bantalan include infrastructure development such as guard houses, water sources and lighting sources of KEM (PLTS) areas. The fields that activities include agriculture (chili, gambas, eggplant, long bean,), fishery (catfish cultivation, indigo) and plantation (citrus, watermelon, banana, coconut). After almost 3 years the value of IPM of KEM Bantalan population increased by ± 40% from the IPM value of early December 2014 period of 49.89 (low category) to 79.69 (middle and upper category) in the period of March 2017. And up to December 2017, Bantalan has reached Rp. 475.581.100, -. This value will continue to grow considering the area of KEM is still productive.